Indonesia Economic Growth Determinant: The Impact of Macro Economic Variables and International Trade - Susanti, Ely; Sholeh, Maimun (International Journal of Economics and Financial Issues, 2020)
The economic growth is one of measurements for a country to be categorized as a developed country. The basic things in economy are monetary stability and fiscal. Monetary stability can be seen from the government's success in controlling inflation flow and restraining interest rates meanwhile fiscal policy can be seen from rate of exchange sector and free trade. Considering those basic conditions, this research is aimed to study the impact of inflation, interest rates, exchange rates, and free trade toward the economy of Indonesia. This research uses data time series from Q1 2009 – Q1 2020 by using Ordinary Least Square (OLS) model. The result of this research shows that interest rates, exchange rates, and import affect the economic growth, meanwhile inflation and export do not affect the economic growth. Keywords: Macroeconomic variable, free trade, economic growth, Indonesia JEL Classifications: E31; E43; F10; F43 DOI: https://doi.org/10.32479/ijefi.10273